(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In cotton ginning enterprises, SBO drying drum is mainly used to dry seeded cotton. By changing the inner part of the SBO drying drum, the seeded cotton can be fed more easily and the seeded cotton drying efficiency is increased.